How Do Price and Quantity Promotions Affect Hedonic Purchases? An ERPs Study - Jing, Kunpeng; Mei, Yupeng; Song, Zhijie; Wang, Hao; Shi, Rui (Frontiers in Neuroscience, 2019)
Due to consuming hedonic products unnecessary to basic well-being, consumers need justifications for pleasure. However, different justifications have differential influences in promotion of hedonic purchases, such as price and quantity promotions (PP and QP), the difference between which is that the latter requires purchasing additional units to get the same discount as the former. In the present study, even-related potentials (ERPs) was applied to revealing timing of brain activities for further understand of how promotion information consisted of promotion type (PP and QP) and discount depth, deep and shallow discounts (DD and SD) on hedonic products was processed. Behaviorally, consumers were more willing to purchase items in PP and DD conditions than QP and SD conditions respectively, and spent more time making final purchase decision in QP and DD condition or PP and SD condition compared to PP and DD condition. Neurophysiologically, DD recruited automatically attentional resources than SD and led a higher P2 amplitude. QP and DD condition or PP and SD condition evoked a larger N2 amplitude and enhanced perceptual conflict compared to PP and DD condition. During late stage, PP and DD elicited a more positive LPP amplitude in contrast to QP and SD respectively, indicating that people have stronger purchase intention and positive affect in PP and DD contexts. These findings provided evidence for the differential influences between PP and QP and what ultimately made consumers buy hedonic products or not.